Education for all girls ; a human right, a social gain : report of The NGO Consultation, 18-19 november 1991 - Friedman, Sara Ann (New York, E.U.A. : UNICEF, 1991)
"NGOS and the advancement of The Education of The Girl Child"
Keywords: Mujeres -- Educación